GOVERNMENT POLICY ANALYSIS IN ADDRESSING JUVENILE DRUG ABUSE CRIMES IN INDONESIA - Riza Zulfikar (AKSELERASI: Jurnal Ilmiah Nasional, 2025)
This study aims to analyse government policies in addressing drug abuse crimes among adolescents and to identify the main challenges as well as the necessary solutions. A normative juridical approach was employed through a literature review of regulations, policy documents, and legal case studies. The findings indicate that although national regulations, such as Law No. 35/2009, support rehabilitative approaches and child protection, implementation remains suboptimal due to weak inter-agency coordination, limited child-friendly rehabilitation facilities, and a lack of understanding among law enforcement officers regarding restorative justice approaches. Additionally, social stigma and family fear of reporting their children are major obstacles, along with insufficient information on available rehabilitation services and inadequate enforcement of existing regulations at the grassroots level. The study recommends policy reform through legislative revision to strengthen rehabilitation efforts and children's rights protection, capacity building for relevant institutions, and the use of digital technology for education and prevention in the community. Furthermore, the development of a nationally coordinated, technology-based system with a humane and adolescent-responsive approach is suggested to ensure more effective and sustainable interventions for the future of Indonesia’s youth.